Pengembangan LKPD Berbasis Liveworksheets Pada Materi Sel Kelas XI Mahidayatul Insan Palangka Raya - Savitri, Shanty; Haryono, Agus; Rahmi, Ennike Gusti; Fahrina, Ririn; Araina, Elga; Uda, Saritha Kittie; Yusiana, Arlinda Amelia; Windasari, Asi (Perspektif Pendidikan dan Keguruan, 2024)
The learning carried out in class XI MA Hidayatul Insan uses LKPD which is still limited and has not supported the learning needs of students, so that the learning that takes place is not optimal, the learning process is less interactive, inspiring, and less motivating students to actively participate. Teachers have not maximized the use of LKPD that is attractive to students. This study aims to determine the structure, feasibility, and student response to LKPD based on Liveworksheet Cell material. This research was conducted in class XI MA Hidayatul Insan Palangka Raya and will use data collection instruments in the form of interview guidelines and to determine the quality of E-LKPD using validation from materials, media experts, and linguists. Based on what has been described, it is necessary to conduct research with the title "Development of Liveworksheet-Based LKPD on Class XI MA Hidayatul Insan Palangka Raya Cell Material". The results of the liveworksheet-based LKPD Development Research were obtained from evaluations conducted by validators of material experts, media experts, and linguists. The quality of the material presented in the LKPD developed with an average score of 77.65% is included in the eligibility criteria. The quality of the LKPD display developed The average percentage of score obtained 80% is included in the feasible criteria and, the quality of the language presented in the LKPD developed with an average score of 98.57% is included in the very feasible criteria. Based on a small-scale trial, the results of students' responses to liveworksheet-based LKPD products showed a very positive response with 97.65%. Thus, it can be concluded that the Development of LKPD Based on Liveworksheets in Class XI Mahidayatul Insan Palangka Raya Cell Material is feasible and stated to be usable in the learning process.